Using Open Broadcaster Software to Improve the Quality of Live Streaming Content on YouTube - Kusuma, Aditya Wahyu; Atmaja, Suhendra; Nihayati, Laila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study examines the use of Open Broadcaster Software (OBS) in enhancing the quality of live streaming content on YouTube from a communication science perspective. The rapid development of digital technology has shifted conventional broadcasting into interactive and real-time live streaming. The key challenge is not only ensuring smooth technical performance but also strengthening audience engagement, communication effectiveness, and two-way interaction. The research employs a descriptive qualitative method with an interpretative approach. Data were collected through in-depth interviews with three gaming content creators on YouTube, direct observation, and literature review. The analysis process followed open coding, axial coding, and selective coding stages. Findings reveal that OBS functions not merely as a technical tool but also as an interactive communication medium. Features such as integrated chat boxes, custom overlays, and donation notifications significantly enhance audience engagement. Communication effectiveness is improved through scene transitions, overlay texts, and visual layouts that make messages clearer and more appealing. Moreover, real-time interaction is facilitated by low latency and seamless integration with YouTube, creating a sense of closeness between streamer and viewers. The high-quality audio-visual output provided by OBS further ensures viewer comfort and fosters the development of an active digital community. In conclusion, OBS improves both the technical and communicative aspects of live streaming by enhancing engagement, communication effectiveness, and real-time interaction. These findings align with the Uses and Gratification theory, which positions audiences as active participants in evaluating content satisfaction.